DETERMINANTS SUSTAINABILITY REPORTING QUALITY ISLAMIC BANKING IN GCC AND SOUTHEAST ASIA - Sisdianto, Ersi; Yuliansyah, Yuliansyah; Razimi, Mohd Syahril Ahmad; Tubarad, Chara Pratami Tidespania (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2025)
This study aims to identify the factors influencing the quality of sustainability reporting in Islamic banks, with a specific focus on dimensions of Islamic corporate governance and sustainability finance. Utilizing panel data from 15 Islamic banks across six countries Bahrain, Qatar, Indonesia, Malaysia, Saudi Arabia, and Oman over seven years (2017–2023), the research employs the Generalized Method of Moments (GMM) estimation to account for dynamic panel bias and potential endogeneity. The findings indicate that Islamic Corporate Sustainability Reports have a significant positive influence on the quality of sustainability disclosure. In contrast, the size of the Board of Commissioners, the Sharia Supervisor Board, the Audit Committee, and the volume of Sustainability Finance did not exhibit statistically significant effects. The model's validity and consistency were confirmed through robust diagnostic tests. The primary limitation lies in the geographical concentration of the sample, which may affect the generalizability of the results. This study contributes to the emerging literature on sustainable finance in Islamic banking by providing empirical evidence on the critical role of structured sustainability reporting, offering practical implications for bank regulators and practitioners to enhance transparency and governance mechanisms for improved stakeholder accountability.